The impact of community activity on the personal resources of low-SES residents: Differences between activists and non-activists. Issue 4 (8th August 2018) - Zanbar, Lea
ABSTRACT: Community social work interventions enable low-SES residents to improve their situation themselves by becoming community activists who design and implement social plans, rather than being passive recipients of welfare services. In addition to aiding themselves and their communities, involvement in this meaningful activity may also enhance the personal resources of activists. Using MANCOVA analyses, the current study compared the levels of seven personal resources, categorized in the literature as capability resources (self-efficacy, self-esteem, mastery, self-actualization) and hardiness resources (resilience, wellbeing, hope), among 200 community activists and 200 non-activists in low-SES communities. The findings reveal significantly higher levels of almost all resources among the activists. Furthermore, regression analyses indicated the significant effect of the activists' years of involvement in community activity and the centrality of the role performed on their personal resources, suggesting that activists' resources are indeed strengthened by their work for the community. The implications for researchers and community social workers are discussed, and practical recommendations are offered.